The use of a fast method of recording Schroeder phase masking function for measuring nonlinear cochlear function - Rahmat, Sarah; O’Beirne, G.A (2014)

(untitled)
Background: A difference in masked thresholds at different scalar factors of the Schroeder masker (the "phase effect") can be observed in normal hearing listeners (Lentz & Leek, 2001). This was believed to be due to intact cochlear non-linearity, but recent findings have suggested a possible contribution of a more central mechanism, presumably the medial olivary cochlear reflex (MOCR) (Wojtczak & Oxenham, 2010). We have recently developed a fast method for recording Schroeder phase masking functions which takes 8 minutes of testing time compared to 45 minutes using the conventional 3 AFC method. Our aim was to use this new method to study the mechanism underlying the phase effect. Methods: 15 normal hearing and 15 sensorineural hearing loss (SNHL) participants were tested. Schroeder phase masking functions were measured at 250 Hz, 500 Hz, 1 kHz, 2 kHz at 45 dB and 75 dB masker levels in all participants, using both on-frequency and off-frequency masking. Results: Phase effects were significantly reduced at low presentation levels and in participants with SNHL as compared to normal hearing participants (p<0.05), consistent with reduction of cochlear nonlinearity in those conditions. The phase effect was present in off-frequency masking and was significantly larger at 1 kHz and 2 kHz than at 500 Hz (p<0.05), supporting potential involvement of the MOCR which is active in off-frequency listening and shows strong effects at frequencies ≥ 1 kHz. Conclusion: The findings were consistent with previous studies, suggesting that our fast method is a useful tool for recording Schroeder phase masking functions and investigating cochlear nonlinearity and the potential involvement of the MOCR in creating the phase effect, specifically at higher frequencies.